2023
DOI: 10.1039/d3cc00953j
|View full text |Cite|
|
Sign up to set email alerts
|

How fast do defects migrate in halide perovskites: insights from on-the-fly machine-learned force fields

Abstract: The migration of defects plays an important role in the stability of halide perovskites. It is challenging to study defect migration with experiments or conventional computer simulations. The former lacks...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The significant cost of these calculations would justify training a model for the defective systems, which can be achieved via fine-tuning ( e.g. training a model for the bulk and then re-training it for relevant configurations of the defective systems 157 ). We highlight that further work is still required to determine the optimal approach for defect MLFF training, particularly regarding the number and diversity of defect configurations required to achieve sufficient accuracies.…”
Section: Challenges and Outlooksmentioning
confidence: 99%
“…The significant cost of these calculations would justify training a model for the defective systems, which can be achieved via fine-tuning ( e.g. training a model for the bulk and then re-training it for relevant configurations of the defective systems 157 ). We highlight that further work is still required to determine the optimal approach for defect MLFF training, particularly regarding the number and diversity of defect configurations required to achieve sufficient accuracies.…”
Section: Challenges and Outlooksmentioning
confidence: 99%
“…The authors found that the nonradiative recombination is accelerated due to the enhanced nonadiabatic coupling and the quantum coherence time is longer as ion migration occurs. Moreover, Tao and co-workers employed the machine learning force field to identify the qualitative trends in migration rates for different defect types and chemical compositions . Liu and co-workers investigated the key factors affecting the efficiency and stability using machine learning and established a mathematical model to predict efficiency based on the fluorescence lifetime and bandgap .…”
mentioning
confidence: 99%
“…Moreover, Tao and co-workers employed the machine learning force field to identify the qualitative trends in migration rates for different defect types and chemical compositions. 100 Liu and co-workers investigated the key factors affecting the efficiency and stability using machine learning and established a mathematical model to predict efficiency based on the fluorescence lifetime and bandgap. 101 Interactions between migrating anions and stationary cations within perovskites have been discussed in several reports.…”
mentioning
confidence: 99%
“… Ø V X + X i This is much higher than the Schottky disorder and thus has received less attention in previous studies. However, research has indicated that aF becomes predominant in MAPbI 3 above 290 K. , The additional aF can probably decompose into I i and V I , leading to a fast ion diffusion , and providing additional charge carrier traps . Nevertheless, the detailed pathways of aF creation and I i diffusion are still in question, especially in the all-inorganic CsPbI 3 perovskite.…”
mentioning
confidence: 99%